Cytotoxic activity of crude saponins from Gaultheria trichophylla against human breast cancer cells MCF-7 and MDA-MB-468 - Fiaz Alam; Qazi Najam us Saqib; Abdul Waheed (Bangladesh Pharmacological Society, 2015)
This study was conducted to evaluate Gaultheria trichophylla crude extract and respective saponins fraction against human breast cancer cell lines. In MTT assay, cell viability was inhibited by G. trichophylla crude extract (500 µg/mL) and saponins (200 µg/mL) in a dose dependent manner with maximum inhibition of (82% and 85%) and (71% and 42%) against MCF-7 and MDA MB-468, respectively. In neutral red uptake assay, the cell viability was inhibited by crude extract and saponins (100 µg/mL) in a similar manner with maximum inhibitions of (96% and 93%) and (87% and 61%) against MCF-7 and MDA MB-468, respectively, with respect to 91% and 93% inhibition by actinomycin-D (4 µM). The DAPI (4',6-diamidino-2-phenylindole) (10 µg/mL) staining of MCF-7 cells treated with crude saponins showed shrunken nuclei with apparent nuclear fragmentation indicating apoptosis and in contrast, MDA MB-468 showed necrosis mode of cell death. The study exhibited that the G. trichophylla provides new evidences to further explore this plant for the novel targets in anticancer drug development.